Pengaruh Corporate Social Responsibility dan Kinerja Keuangan Terhadap Nilai Perusahaan - Pramono, Hadi; Fakhruddin, Iwan; Hapsari, Ira (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2022)
This study purpose to empirically examine the effect of Corporate Social Responsibility (CSR) and Financial Performance on Firm Value. Company value is an assessment of public trust in a company which is reflected in the stock price. The higher the value of the company, the level of prosperity of shareholders also increases. Company value is measured using Tobin’s Q, CSR is measured using content analysis, and ROA measures financial performance. Using the purposive sampling method, the research sample is manufacturing companies listed on the Indonesia Stock Exchange from 2018-2021. The results of the study indicate that CSR and Financial Performance have a positive effect on firm value.